On becoming a better therapist - Duncan, Barry L. (American Psychological Association, 2010)
Provides simple but elegant solutions for becoming a more effective therapist. Redirects our attention from specific treatments to our behavior and attitudes as therapists, offering a refreshing look at improving treatment that operates outside the contemporary solution of providing the "right psychological treatment for the right disorder." Emphasizes the therapist and the therapist's contribution to patient well-being, extending the usual solutions provided in graduate education and challenging therapists in two important ways: 1) requires therapists to systematically monitor their clients' treatment response and the therapeutic alliance (as rated by the client) and to discuss these phenomena with the client and 2) therapists must examine their effectiveness over time and use this information to become more effective. The discourse is on the one hand highly personal, anecdotal, passionate, and persuasive, and on the other, evidence-based